Concentration effect on optical properties of CDots composite film from sugar (sucrose). Issue 1 (February 2021) - Rahmawati, F; Isnaeni,; Lewa, I W L; Iriani, Y
Abstract: Carbon dots (CDots) are one of the fascinated carbon-based nanomaterials which have broad applications. One fields that rarely been explored is using Cdots as a composite luminescence film with addition of polyvinyl alcohol (PVA). The luminescence properties of Cdots is a great potential that can be used to make luminescence PVA/CDots films since CDots are known as materials that have strong luminescence. This study aims to determine the effect of CDots concentration on the optical properties of Cdots/PVA composite. We also observed the effect of excitation wavelengths to emission of CDots/PVA composite. The carbon dots was synthesized from commercial sugar using microwave technique. UV-Vis spectroscopy characterization showed that the concentration of CDots affect to surface state of CDots. Surface energy bands from individual CDots may overlap one to another creating new energy level, so that the absorbance peak experiences red shift. Photoluminescence spectra results showed that the excitation wavelength caused a difference in the emission wavelength in the sample. Excitation with a blue laser produces green emissions while excitation with a green laser produces red emissions. The results show that the synthesized Cdots have potential to be used as luminescence films. The as-synthesized Cdots shows great luminescence properties and can be varied with several controlled parameters.